PENGARUH DIGITAL SIGNAGE TERHADAP PERILAKU KONSUMEN DENGAN AFEK POSITIF SEBAGAI VARIABEL MEDIASI PADA SUZUYA MALL SEUTUI DI KOTA BANDA ACEH - Nanda Sulfia Putri, Syarifah Evi Zuhra (Departemen Manajemen, 2017)
This research aims to ascertain the impact of digital signage toward consumer behavior. The sample used in this study are the custumers of Suzuya Mall Banda Aceh. The used research method utilized questionnaires as the research instrument. The amount of questionnaires that had been analyzed were 100 questionnaires. Non probability sampling system had been used for sampling tehnique. This tehnique used to the unknown element profitability within the population that was selected as the sample. Partial Least Square was also as analysis method to ascertain the impact from involved variables. The results showed that, (1) The Digital Signage significantly takes effect to Consumer Behavior, (2) Digital Signage significantly takes effect to Positive Affect, (3) the Positive Affect significantly takes effect to Consumer Behavior, (4) The Digital Signage significantly takes effect to Consumer Behavior mediated by Positive Affect as mediation variable. Keyword: Digital Signage, Consumer Behavior, Positive Affect